Innovation of Kiai Leadership in Forming the Ecopreneurial Spirit Santri - Nur Arifah (Jurnal Multidisiplin Madani, 2024)
Kiai's leadership innovations in forming the ecopreneur spirit of santri is started by ecopreneur activities which are new ideas that have been launched by the kiai as a balance between religious activities and skill activities, resulting in producing Islamic boarding school graduates who are clever in the field of religion and have an entrepreneurial spirit who cares about the environment